Stainless steel in swimming pool buildings : a guide to selection and use. (Nickel Development Institute, 1995)
This guide explains the background of issues related to stress corrosion cracking of some stainless steels and gives practical advice on the successful use of stainless steel. It is aimed at architects, designers, builders and pool managers.